Dispensa discriminatória de trabalhadores sob a perspectiva dos direitos fundamentais - Lima, Ana Lúcia Coelho de (2008)
This study is intended to verify if the employee discriminatory dismissal under the perspective of fundamental rights. Thus, it uses a transdisciplinary approach which presents the Constitutional Law, Labour Law and Civil Law as object of analysis. It comprehends the contemporary concept over human rights and fundamental rights, as well as the role of the fundamental principles in making social laws effective, in order to find the source of discrimination at work, the moment and ways through which it may occur. It also establishes the concepts and differences among the redundancy and arbitrary dismissal, as well as the abusive and discriminatory dismissal, based on the Convention n° 158 of the I nternational Labour Organization (ILO) and theory of abuse in the light of the 2002 Civil Code. Results from the research demonstrate that discriminatory dismissal is forbidden, as it is an act that transcends the regular employer-employee relationship. It is an act that directly affects an amount of major interests belonging to the State and society, in a total affront to the fundamental rights. Finally, this study highlights some hipothesis about discriminatory dismissal and the actions of the Ministry of Labour to defeat this type of dismissal.